Lipids From Trypanosoma cruzi Amastigotes of RA and K98 Strains Generate a Pro-inflammatory Response via TLR2/6 - Bott, Emanuel; Carneiro, Alan B.; Gimenez, Guadalupe; López, María G.; Lammel, Estela M.; Atella, Georgia C.; Bozza, Patricia T.; Belaunzarán, María L. (Frontiers in Cellular and Infection Microbiology, 2018)
Lipids from microorganisms are ligands of Toll like receptors (TLRs) and modulate the innate immune response. Herein, we analyze in vitro the effect of total lipid extracts from Trypanosoma cruzi amastigotes of RA and K98 strains (with polar biological behavior) on the induction of the inflammatory response and the involvement of TLRs in this process. We demonstrated that total lipid extracts from both strains induced lipid body formation, cyclooxygenase-2 expression and TNF-α and nitric oxide release in macrophages, as well as NF-κB activation and IL-8 release in HEK cells specifically through a TLR2/6 dependent pathway. We also evaluated the inflammatory response induced by total lipid extracts obtained from lysed parasites that were overnight incubated to allow the action of parasite hydrolytic enzymes, such as Phospholipase A1, over endogenous phospholipids. After incubation, these total lipid extracts showed a significantly reduced pro-inflammatory response, which could be attributed to the changes in the content of known bioactive lipid molecules like lysophospholipids and fatty acids, here reported. Moreover, analyses of total fatty acids in each lipid extract were performed by gas chromatography-mass spectrometry. Our results indicate a relevant role of T. cruzi lipids in the induction of a pro-inflammatory response through the TLR2/6 pathway that could contribute to the modulation of the immune response and host survival.